Could geoengineering research help answer one of the biggest questions in climate science?. Issue 7 (13th July 2017) - Wood, Robert; Ackerman, Thomas; Rasch, Philip; Wanser, Kelly
Abstract: Anthropogenic aerosol impacts on clouds constitute the largest source of uncertainty in quantifying the radiative forcing of climate, and hinders our ability to determine Earth's climate sensitivity to greenhouse gas increases. Representation of aerosol–cloud interactions in global models is particularly challenging because these interactions occur on typically unresolved scales. Observational studies show influences of aerosol on clouds, but correlations between aerosol and clouds are insufficient to constrain aerosol forcing because of the difficulty in separating aerosol and meteorological impacts. In this commentary, we argue that this current impasse may be overcome with the development of approaches to conduct control experiments whereby aerosol particle perturbations can be introduced into patches of marine low clouds in a systematic manner. Such cloud perturbation experiments constitute a fresh approach to climate science and would provide unprecedented data to untangle the effects of aerosol particles on cloud microphysics and the resulting reflection of solar radiation by clouds. The control experiments would provide a critical test of high‐resolution models that are used to develop an improved representation aerosol–cloud interactions needed to better constrain aerosol forcing in global climate models. Key Points: Anthropogenic aerosol impacts on clouds constitute the largest source of uncertainty in quantifying radiative forcing of climate A lack of control conditions for anthropogenically perturbed clouds has led to an impasse in separating aerosol from meteorological impacts Controlled aerosol perturbation experiments would overcome an impasse in constraining aerosol–cloud interactions using observations